Circulating miRNA‐375 as a potential novel biomarker for active Kaposi's sarcoma in AIDS patients. Issue 2 (13th December 2018) - Piano, Maria Assunta; Gianesello, Lisa; Grassi, Angela; Del Bianco, Paola; Mattiolo, Adriana; Cattelan, Anna Maria; Sasset, Lolita; Zanovello, Paola; Calabrò, Maria Luisa
Abstract: The aim of this study was to identify circulating microRNAs (miRNAs) that could be used as biomarkers in patients at risk for or affected by AIDS‐Kaposi's sarcoma (KS). Screening of 377 miRNAs was performed using low‐density arrays in pooled plasma samples of 10 HIV/human herpesvirus 8 (HHV8)‐infected asymptomatic and 10 AIDS‐KS patients before and after successful combined antiretroviral therapy (cART). MiR‐375 was identified as a potential marker of active KS, being the most down‐regulated in AIDS‐KS patients after cART and the most up‐regulated in naïve AIDS‐KS patients compared to naïve asymptomatic subjects. Validation on individual plasma samples confirmed that miR‐375 levels were higher in AIDS‐KS compared to asymptomatic patients, decreased after cART‐induced remission in most AIDS‐KS patients and increased in patients with active KS. In asymptomatic patients miR‐375 was up‐regulated after cART in both screening and validation. Statistical analyses revealed an association between miR‐375 changes and CD4 cell counts, which could explain the discordant cases and the opposite trend between asymptomatic and AIDS‐KS patients. These data suggest that circulating miR‐375 might be a good indicator of active AIDS‐KS. Moreover, changes in miR‐375 levels may have a prognostic value in HIV/HHV8‐infected patients undergoing treatment. Further large‐scale validation is needed.